Ekologi dan Keanekaragaman Flora di Pulau Enggano - Dhanang Puspita; Sigit Eko Prasetyo (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2020)
Enggano Island is one of the islands in Indonesia and is a human settlement. Enggano Island is geologically an ocean island and according to history, it has never joined the Sumatera island. Thus Enggano Island is estimated to have a unique ecosystem and endemic organisms. The purpose of this research is to study the ecology of Enggano Island and its diversity of flora. The method used is exploration, field survey, interview and literature study. The results of this study showed that Enggano Island has five ecosystems, consist of mangrove forest, coastal forest, riparian, forest, and freshwater swamp. Each ecosystem has a specific plant in accordance with the character of its habitat.